Civil society in comparative perspective - Enjolras, Bernard; Sivesind, Karl Henrik, 1962- (Comparative social research ;, 2009)
This book presents a collection of comparative studies of civil society around two main issues: the comparison and analysis of civil society regimes in relation to different constructions of citizenship and welfare states and the role of civil society in governance and active participation of citizens. The first part of the book is concerned with comparisons of civil society institutional frameworks and regimes. In this section the contributions address the ways institutional cross-countries comparisons may be undertaken and discuss the extent to which common trends or divergent tendencies characterize national civil societies. The second part focuses on the role of civil society as a vector of citizens' participation and as an avenue for democracy. Democratic citizenship is often considered as requiring, in addition to a set of formal rights and obligations, a public sphere within which citizens can actively participate within and beyond the state. Building on international comparisons the articles in this section discuss the extent to and the modalities by which civil society is crucial to the functioning of democracy and the plain exercise of citizenship.